DJ‐1 modulates mitochondrial response to oxidative stress: clues from a novel diagnosis of PARK7. Issue 1 (6th October 2016) - Di Nottia, M.; Masciullo, M.; Verrigni, D.; Petrillo, S.; Modoni, A.; Rizzo, V.; Di Giuda, D.; Rizza, T.; Niceta, M.; Torraco, A.; Bianchi, M.; Santoro, M.; et al.
Abstract : Abstract : DJ‐1 mutations are associated to early‐onset Parkinson's disease and accounts for about 1–2% of the genetic forms. The protein is involved in many biological processes and its role in mitochondrial regulation is gaining great interest, even if its function in mitochondria is still unclear. We describe a 47‐year‐old woman affected by a multisystem disorder characterized by progressive, early‐onset parkinsonism plus distal spinal amyotrophy, cataracts and sensory‐neural deafness associated with a novel homozygous c.461C>A [p.T154K] mutation in DJ‐1 . Patient's cultured fibroblasts showed low ATP synthesis, high ROS levels and reduced amount of some subunits of mitochondrial complex I; biomarkers of oxidative stress also resulted abnormal in patient's blood. The clinical pattern of multisystem involvement and the biochemical findings in our patient highlight the role for DJ‐1 in modulating mitochondrial response against oxidative stress.